STRATEGI KOMUNIKASI PEMASARAN PRODUK MELALUI PROGRAM BEASISWA IDCLOUDHOST 2023 - ', Vinolawati; Awza, Rusmadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The 2023 IDCloudHost Scholarship Program is a program in collaboration with Telkom University to finance further studies in undergraduate programs at Telkom University colleges. The 2023 IDCloudHost Scholarship is utilized by PT. Cloud Hosting Indonesia (IDCloudHost) as a product marketing strategy sees many applicants for the IDCloudHost scholarship program from year to year. This research aims to analyze the formulation, understand implementation, and examine the evaluation of communication strategies in product marketing through the IDCloudHost 2023 scholarship program. This research uses Fred R. David's strategy concept, which is divided into three stages. Uses qualitative methods to produce descriptive data. Meanwhile, determining research subjects uses purposive techniques. There were 7 informants in this study. Data collection techniques in this research were through interviews, observation and documentation. Then for data analysis techniques use the analysis proposed by miles and Huberman includes data collection, data reduction, data presentation, and drawing conclusions. Data validity checking techniques include triangulation and participation. The results of this research show that in the formulation, the communicator was Event & Program staff and someone recruited by IDCloudHost. Communicants are high school, vocational school graduates, gap year students, and first-semester students with a maximum age of 22 years. The message is information about scholarships and products that IDCloudHost has. The media used are Instagram, Facebook, Twitter, TikTok, YouTube, website and email. The effect is that the information is conveyed well by the audience and the targets that IDCloudHost wants to achieve are met. The implementation is creating content in all media, launching advertisements, holding events, and distributing marketing emails. The next evaluation is to be able to compare the increase from year to year and conduct a survey to find out how much the number of applicants for the 2023 IDCloudHost scholarship has increased. Keywords: Communication Strategy, Product Marketing, IDCloudHost Scholarship Program 2023.